(untitled) (Journal of Renal and Hepatic Disorders, 2023)
Hepatitis A is a common viral infection worldwide that is transmitted via the fecal-oral route. Since the introduction of an efficient vaccine, the incidence of infection has decreased but the number of cases has risen due to widespread community outbreaks among unimmunized individuals. Classic symptoms include fever, malaise, dark urine, and jaundice, and are more common in older children and adults. People are often most infectious 14 days prior to and 7 days following the onset of jaundice. We will discuss the case of a young male patient, diagnosed with acute hepatitis A, leading to fulminant hepatitis refractory to conventional therapy and the development of subsequent kidney injury. The medical treatment through the course of hospitalization was challenging and included the use of L-ornithine-L-aspartate and prolonged intermittent hemodialysis, leading to a remarkable outcome. Hepatitis A is usually self-limited and vaccine-preventable; supportive care is often sufficient for treatment, and chronic infection or chronic liver disease rarely develops. However, fulminant hepatitis, although rare, can be very challenging to manage as in the case of our patient.